Effects of yoga training in post-menopausal women - Gronek, Joanna; Domaszewska, Katarzyna (Akademia Wychowania Fizycznego w Poznaniu)
Aging is a multietiological process and a major risk factor for chronic diseases including geriatric. In the healthy aging, the proper implementation of exercise to improve disease-related symptoms and comorbidities in the general population is a high priority. However, there is still a gap concerning studies analyzing influence of yoga in older people especially in post-menopausal women. Therefore, the aim of this mini review is a brief summary of well-established findings in yoga as an exercise intervention. In this paper, we conducted a narrative mini review of the influence of practising yoga on aging especially in post-menopausal women, searching the online databases: Web of Science, PubMed and Google Scholar, and, subsequently, discuss possible mechanisms of this action. On the basis of this review, it is evident that practising the yoga seems to be a promising intervention especially recommended for the elderly.
Keywords: training; yoga; neurotrophic factors; post-menopausal women